Clinical Outcomes for Patients With Metastatic Breast Cancer Treated With Immunotherapy Agents in Phase I Clinical Trials - Schreiber, Anna R.; Kagihara, Jodi A.; Weiss, Jennifer A.; Nicklawsky, Andrew; Gao, Dexiang; Borges, Virginia F.; Kabos, Peter; Diamond, Jennifer R. (Frontiers in Oncology, 2021)
Background: Immuno-oncology (IO) agents have demonstrated efficacy across many tumor types and have led to change in standard of care. In breast cancer, atezolizumab and pembrolizumab were recently FDA-approved in combination with chemotherapy specifically for patients with PD-L1-positive metastatic triple-negative breast cancer (TNBC). However, the single agent PD-1/PD-L1 inhibitors demonstrate only modest single agent efficacy in breast cancer. The purpose of this study was to investigate the efficacy of novel IO agents in patients with metastatic breast cancer (MBC), beyond TNBC, treated in phase I clinical trials at the University of Colorado. Methods: We performed a retrospective analysis using a database of patients with MBC who received treatment with IO agents in phase I/Ib clinical trials at the University of Colorado Hospital from January 1, 2012 to July 1, 2018. Patient demographics, treatments and clinical outcomes were obtained. Results: We identified 43 patients treated with an IO agent either as a single agent or in combination. The average age was 53 years; 55.8% had hormone receptor-positive/HER2-negative breast cancer, 39.5% TNBC and 4.7% HER2-positive. Patients received an average of 2 prior lines of chemotherapy (range 0-7) in the metastatic setting. Most patients (72.1%) received IO alone and 27.9% received IO plus chemotherapy. Median progression-free survival (PFS) was 2.3 months and median overall survival (OS) was 12.1 months. Patients remaining on study > 6 months (20.9%) were more likely to be treated with chemotherapy plus IO compared to patients with a PFS < 6 months (77.8% v. 14.7%). No differences in number of metastatic sites, prior lines of chemotherapy, breast cancer subtype, absolute lymphocyte count, or LDH were identified between patients with a PFS > 6 months vs. < 6 months. Conclusions: Our phase I experience demonstrates benefit from IO therapy that was not limited to patients with TNBC and confirms improved efficacy from IO agents in combination with chemotherapy. A subset of patients with MBC treated in phase I clinical trials with an IO agent derived prolonged clinical benefit. Predictors of response to immunotherapy in breast cancer remain uncharacterized and further research is needed to identify these factors.